Is Spiritual Intelligence (SQ) or Spiritual Quotient an Intelligence? Howard Gardner's Theory of Multiple Intelligences analyzed. - Moleka, Pitshou, Basikabio (My University, 2021)
The concept of spiritual intelligence is currently at the focus of scientific debate. One of the most important problems is if it is a valid intelligence that meets the criteria developed by scholars. In this paper, I look at this idea in the context of Howard Gardner's theory of multiple intelligences and show some evidence from biology, neurology, and other scientific disciplines.
Keywords: spiritual intelligence; spiritual quotient; Howard Gardner's Theory; Multiple Intelligence